Advaita epistemology and metaphysics : an outline of Indian non-realism - Ram-Prasad, Chakravarthi (RoutledgeCurzon, 2002)
Based on original translations of passages from the works of three major thinkers of the classical Indian school of Advaita (Sankara, Vacaspati and Sri Harsa), but addressing issues found in Descartes, Berkeley, Hume, Kant, Wittgenstein and contemporary analytic philosophers, this book argues for a philosophical position it calls 'non-realism'. This is the view that an independent, external world must be assumed if the features of cognition are to be explained, but that it cannot be proved that there is such a world, independently of an appeal to cognition itself. This position is constructed.